2017
DOI: 10.1007/s00339-017-1064-5
|View full text |Cite
|
Sign up to set email alerts
|

New insight into nanoparticle precipitation by electron beams in borosilicate glasses

Abstract: Nanoprecipitation in different oxide glasses by means of electron irradiation in transmission electron microscopy (TEM) has been compared in this study. Upon irradiation, groups or patterns of nanoparticles with various morphologies and sizes were formed in borosilicate glasses, loaded with zinc, copper, and silver. The study successfully includes loading ranges for the target metal from doping level (1%) over medium level (20%) to majority phase (60%). It is found that particle patterning resolution is affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Small particles were observed in the BF images of electron irradiated SNB1 and SNB2 as shown in Figures and , respectively. Similar particles were occasionally reported . Sun et al studied the electron irradiation damage in sodium borosilicate, iron phosphate and aluminophosphate glass waste forms by using TEM and observed nanocrystals in a borosilicate glass (17.78 wt% B 2 O 3 –15.83 wt% Na 2 O–61.39 wt% SiO 2 –4.99 wt% Fe 2 O 3 ).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Small particles were observed in the BF images of electron irradiated SNB1 and SNB2 as shown in Figures and , respectively. Similar particles were occasionally reported . Sun et al studied the electron irradiation damage in sodium borosilicate, iron phosphate and aluminophosphate glass waste forms by using TEM and observed nanocrystals in a borosilicate glass (17.78 wt% B 2 O 3 –15.83 wt% Na 2 O–61.39 wt% SiO 2 –4.99 wt% Fe 2 O 3 ).…”
Section: Discussionsupporting
confidence: 62%
“…Sun et al studied the electron irradiation damage in sodium borosilicate, iron phosphate and aluminophosphate glass waste forms by using TEM and observed nanocrystals in a borosilicate glass (17.78 wt% B 2 O 3 –15.83 wt% Na 2 O–61.39 wt% SiO 2 –4.99 wt% Fe 2 O 3 ). Sabri et al studied the nanoprecipitation in borosilicate glasses loaded with Zr, Cu and Ag . They observed amorphous phase separation and parallel nanoparticle precipitation, and found that heating alone without electron irradiation did not result in the precipitation of nanoparticles .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, these two mechanisms can easily scramble an ordered structure into a disordered state by randomly displacing atoms, but it is not obvious why they can also drive the randomly displaced atoms into a new and ordered structure (or phase). Temperature rise due to the energy deposit may be a possibility [7], but most experimental evidences strongly suggest that the precipitation be a result of an athermal crystallization process [3,[8][9][10].Thermodynamically, the precipitation (or phase transformation) is driven by lowering the Gibbs free energy of system. However, in (S)TEM, electron irradiation continuously injects energy into the specimen.…”
mentioning
confidence: 99%